English language toolbox: Proverbs - Kirkpatrick, Elizabeth McLaren (Learners Pub. Singapore, 2003)
Proverbs are by far the richest man's prominence being a privilege and a multifaceted reflection of communication activities. They serve the presence of an ongoing process of mentality as effective spoken or written instruments conveying countless senses, intentions, experiences, purposes and so on. This paper aims to explore the significance of proverbs at various levels of communications through a thorough depiction of the essential traits and various possible inherent and intended meanings which they convey. It is mainly concerned with viewing the communicative significance of proverbs through involving them to the possible speech acts they intend to provoke and through expounding the multiple congenital meanings which they imply when used in a communicative situation. It can be explicitly demonstrated through this paper that proverbs are used as an intrinsic estimation of the communication process emphasizing different values of instructive functions, moral considerations, knowledges, wisdoms and experiences at and for the will of human being.